Intra-Articular Hyaluronic Acid for Knee Osteoarthritis: A Postmarket, Open-Label, Long-Term Historical Control Study with Analysis Detailed per Krellgren-Lawrence Radiologic Osteoarthritis Scale Grade - Patrice Vincent, MEng; Thibaut Lucas de Couville, MSc; Thierry Thomas, MD (Elsevier, 2020)
ABSTRACT: Background: Intra-articular injections of hyaluronic acid-also called viscosupplementation (VS)-is frequently used for the symptomatic treatment of knee osteoarthritis, a painful and debilitating long-term disease, affecting an important fraction of elderly populations. Severity of knee osteoarthritis is generally described by Kellgren-Lawrence (KL) radiological classification. VS has been widely studied in many clinical trials; however, the results are rarely analyzed in detail according to KL grade. Method: A large, clinical, open-label study was performed in 2004-2007 on 1177 patients with knee osteoarthritis, each treated with VS consisting of 3 injections of Arthrum H 2% (LCA Pharmaceutical, Chartres, France). The characteristics of the patients at baseline included demographic profile, body mass index, KL grade, and clinical scores for pain and function using the Western Ontario and McMaster Universities index. Follow-up visits were at 3, 6, and 9 months after VS procedure. This large database was entirely reprocessed in 2019 to provide a separate analysis per KL grade, complemented by the assessment of the Outcome Measures in Rheumatoid Arthritis Clinical Trials-Osteoarthritis Research Society International rates (%) of responders to the treatment. The analysis was carried out for both intention-to-treat and per-protocol completer populations. Results: A primary outcome in the intention-to-treat analysis, variations of the Western Ontario and McMaster Universities index pain subscore from inclusion to the end of the study were 19.8, 19.8, 17.8, and 14.2 for KL grade I to KL grade IV patients, respectively, on a 0 to 100 scale. In the per-protocol analysis, under the same conditions, the variations were 20.6, 19.9, 17.1, and 11.7. All results were significant (P < 0.001) and clinically relevant for each KL grade. Significant improvements were also observed for the Western Ontario and McMaster Universities index function subscore and for the other secondary outcomes. The Outcome Measures in Rheumatoid Arthritis Clinical Trials-Osteoarthritis Research Society International responders rate reached 72% to 82% for KL grade I through III patients at Month 6 and Month 9. For KL grade IV patients, the maximum rate reached was 47.7% at Month 6. There was evidence that KL grade is a critical parameter, particularly if KL grade IV is present. Other parameters such as gender, body mass index, and age were not identified as prognostic factors of response to VS based on χ2 and odds ratio (95% CI) testing. Conclusions: Detailed analysis by KL grade supports that VS treatment with Arthrum H 2% applies to a large variety of patients with knee osteoarthritis.